Internal and External Criticism of the History of Leadership Hadith: A Case Study in the Book of Sahih Bukhari and Muslims - Maulidi, Affan; Moh.Mujib (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The hadith on leadership stating that political authority belongs to the Quraysh tribe constitutes one of the key narrations in classical Islamic political thought. This narration is recorded in Sahih al-Bukhari and Sahih Muslim, and has long been understood as a normative foundation for the theory of imamah as well as a justification for genealogical requirements of leadership within the discourse of fiqh siyasah. However, in the context of modern politics, characterized by the nation-state system, democracy, and the principle of equality, the interpretation of this hadith requires a more proportional methodological approach. This study aims to analyze the hadith of Quraysh leadership through the approaches of sanad (chain of transmission) and matan (textual) criticism. It is a library-based research employing a descriptive-analytical method, examining transmission chains, the credibility of narrators, textual structure, and the socio-historical context of the hadith’s emergence. The findings indicate that the hadith is authentic in terms of sanad, yet context-dependent in terms of matan. The reference to Quraysh reflects the socio-political reality of early Islam rather than a universal normative rule. Therefore, the hadith is better understood as conveying leadership values, such as legitimacy, capacity, and responsibility, rather than prescribing rigid genealogical requirements, thus maintaining its relevance in contemporary political contexts.